PERANCANGAN TAS SELEMPANG BONGGOL JAGUNG DENGAN CITRA ELEGAN : DESIGN OF CORN COB SLING BAG WITH AN ELEGANT IMAGE - Rasyida, Zakia; Andry; Nefo, Amirul (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2025)
This research is a design that aims to produce a corn cob bag with an elegant image obtained from the results of a search for a figure's furniture style choices, in this case represented by Maria Rahajeng as a representation of the target market that has been set. This research is motivated by the discrepancy between the Willingness to pay of consumers with the design and price of previously designed products. The findings from the previous design were to create a cellphone sling bag with a more varied design and use safer covers and materials. The method used in this design is the design thinking method, which begins with the empathize process and ends with the test process. At the end of the study, the output was produced in the form of a Prototype, namely a Sling Bag which was tested on the target market through an exhibition in the city of Bandung. Most of the research was conducted at PT. Matahati Kreasi Nusantara, Bandung, West Java, and was carried out for approximately 4 months. The novelty of this research is the use of corn cob material as the raw material for bags with an elegant image. The end of this research produced a prototype bag with an elegant image that has been tested at a local exhibition in the city of Bandung.